Broadcast Media Messages on Pedophilia and Audience Responsibility - Chime-Nganya, Chioma Rose; Nsude, Ifeyinwa (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
Broadcast media has the power to inform and mobilize communities on the issue of pedophilia. By focusing on education, support, and community responsibility, media messages can contribute to a culture that protects children and fosters safe environments. Advancement in technology has brought with it some notable innovations in information dissemination one of which is through broadcast media. The paper pointed out that Nigeria like other countries of the world is presently grasping with this societal menace that is threatening the future of our children and that of the values that we cherish as a nation. Hardly a week passes by without hearing some cases relating to pedophilia in the Nigerian media, even the churches and mosques are not spared either, it is indeed a pandemic that have left its victim in pitiable state; and the sadistic reality about sex treatment deviating from adults towards children, is very appalling. The female sex seems to be the most endangered; they are endangered from birth because the Nigerian society treats the birth of the girl child with contempt and gaiety. This paper adopted Moral Responsibility theory. The paper concludes that child safety is a priority that requires everyone’s attention. Pedophilia and child abuse are real risks, but by understanding the warning signs, talking openly with our children, and taking responsible actions, we can protect the vulnerable.